Hepatic extravasation complicated by umbilical venous catheterization in neonates: A 5-year, single-center experience - Hsin-Jen Chen; Hsun-Chin Chao; Ming-Chou Chiang; Shih-Ming Chu (Pediatrics and Neonatology)
Background: Care of newborns in the neonatal intensive care unit generally involves umbilical venous catheterization (UVC) for central vein access to enable medical needs. The study aimed to evaluate the sonographic appearance, risk factors, and outcomes of UVC-related hepatic extravasation (HE) in neonates. Methods: A 5-year retrospective study where 33 neonates were enrolled with a diagnosis age ranging from 2 to 25 days. 78.8% of the subjects had UVC malpositioning shown on initial radiography. All neonates sonographically diagnosed with HE, and follow-up ultrasound (US) was performed. Results: The main findings of HE on US were hyperechoic or heterogeneous lesions of a lobulated (51.7%) or wedge shape (48.3%), located mainly in the left lobe (72.7%). The mean time to resolution of HE was 2.25 months. Seven (21.2%) patients showed hepatic vascular thrombosis at follow-up. Two (6%) patients had abnormal liver function, which subsequently normalized. Conclusion: Malposition of the UV catheter was the predisposing factor for UVC-related HE in neonates. US facilitates detection of UVC malpositioning and diagnosis of HE, as well as delayed complications. A shorter duration of UVC placement is associated with favorable outcomes of UVC-related HE in neonates. Key Words: hepatic extravasation, neonate, ultrasound, umbilical vein catheterization